Peningkatan Kemampuan Pemecahan Masalah Siswa Melalui Implementasi Pendekatan PMRI Berbasis Diskusi Kelompok - Trisna Jayantika, I Gusti Agung Ngurah; Kesumawati, Ni Wayan Ayu; Septiani, Ni Made Ari (SAP (Susunan Artikel Pendidikan), 2024)
Studies have demonstrated that students' problem-solving skills in Indonesia are still relatively low, necessitating a transformation in teaching methods to enhance these skills. This study aims to assess the implementation of the Indonesian Realistic Mathematics Education (PMRI) approach based on group discussions in improving students' mathematical problem-solving skills. This research is a Classroom Action Research (CAR) focused on improving the mathematical problem-solving skills of 36 students in class XI MIPA 5 at SMA Negeri 3 Denpasar. The implementation method is divided into two cycles with data collection techniques using mathematical problem-solving skills tests and observation sheets. The analysis of students' mathematical problem-solving skills in each cycle resulted in a percentage of students who achieved or exceeded the minimum mastery criteria score of 75. The results showed that the average score of all students in the Pre-Cycle stage was 30.72; the average score of all students in Cycle I reached 66.94; the average score of all students in Cycle II also showed a significant increase, reaching 81.22. The implications of this study highlight the importance of utilizing realistic problems in learning, such as PMRI, as well as group discussion methods with peer tutors in enhancing students' mathematical problem-solving skills.